Adult education: a tale of empowerment denied - Ramachandran, Vimala (1999)
The National Adult Education Programme and the Total Literacy Campaign (TLC) failed to live up to their initial promise. Corruption undermined the former, a grants-in-aid scheme, and a quick-fix approach the latter, besides the stress on the commitment of individual administrators rather than on system reform that injured both. One upshot was that an opportunity for the empowerment of women that unexpectedly presented itself was squandered. - Reproduced
Keywords: Education - India; Adult education - India; Adult education